Impact of an intervention on the hand hygiene compliance rates in paediatric surgical intensive care units in two tertiary care hospitals - Ramadan, Moustapha; Hamza, Wafaa; Alfadhli, Mariam (International Journal of Infection Control, 2018)
Hand hygiene (HH) is comprehensively recognized to be the single most significant measure to prevent cross-transmission of microorganisms between patients. This study aimed to measure the HH compliance rates baseline, identify the barriers for HH non-compliance and to assess the impact of multidisciplinary intervention. An interventional study conducted from March 2017 to July 2017 in two surgical paediatric intensive care units (PICU) in two tertiary care hospitals. Root Cause Analysis (RCA) was used for identification of the barriers that affect HH compliance followed by intervention included HH training and education, video presentations in the hospital internal circuit, visual cues, using a code word for gentle verbal reminding and HH champions for follow up. Direct observation of HH was done before and after the intervention applying the WHO HH observation method. HH compliance rate was calculated by dividing the number of HH actions by the total number of opportunities. Chi-square (χ2) test was used to identify statistical significance. A total of 1735 HH opportunities were observed during all phases of the study. RCA identified skin dryness, forgetfulness and work intensity as the commonest barriers for non-compliance. Significant improvement was observed among all groups in PICU A (+23%; p value <0.001); (+19% for nurses, +29 % for doctors, and +36% for others; p value <0.001). While significant improvement was reported among doctors (+28%; p value <0.001) in PICU B. Improvement in HH compliance is achievable by multidisciplinary intervention. Providing continuous intensified training and feedback is essential to maintain high level of HH compliance.